2017
DOI: 10.1111/jce.13185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Impedance Surrounding a Radiofrequency Ablation Catheter Electrode on Lesion Characteristics

Abstract: Environmental Impedance and Ablation Lesions Introduction The electrical conductivity of the environment surrounding a catheter electrode may affect radiofrequency (RF) current. A higher impedance environment enveloping a catheter tip can be insulating and thus direct RF preferentially into targeted cardiac tissue. We sought to evaluate whether different environmental impedances will affect RF lesions. Methods An ex vivo model using bovine myocardium, load cell, and 4 mm ablation catheter was tested using a ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Nguyen and colleagues1, 2, 3 have compared RF lesion size with NS, half NS, and D5W irrigation in preclinical animal models. D5W was found with the largest lesions as compared to the former 2 fluids, which has been attributed to decreased dispersion or shunting of energy that may result with an ionic charged solution, decreasing the local impedance field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen and colleagues1, 2, 3 have compared RF lesion size with NS, half NS, and D5W irrigation in preclinical animal models. D5W was found with the largest lesions as compared to the former 2 fluids, which has been attributed to decreased dispersion or shunting of energy that may result with an ionic charged solution, decreasing the local impedance field.…”
Section: Discussionmentioning
confidence: 99%
“…The potential complication of D5W irrigation is higher incidence of steam pops (50/80 applications) when using high power (50 W) and a perpendicular position 1 ; we applied lower power and parallel touch in this case, which may help avoid the risk. Meanwhile, for achieving deeper lesions, we increased the impedance cutoff to improve the efficacy of RF energy delivery 3 . Whether increasing to high power may have been equally as effective as changing the irrigant, our clinical experience has shown rapid increases in temperature that impair continued RF when ablating within the coronary venous system.…”
Section: Discussionmentioning
confidence: 99%
“…Additional ex vivo and in vivo studies have confirmed that increased fluid in the pericardial space leads to smaller lesion formation and that a higher impedance fluid in this same space can facilitate effective delivery of RF ablation to the myocardium. 25…”
Section: Pericardial Spacementioning
confidence: 99%
“…Decreasing the ionic concentration of the irrigant by using a fluid such as half-normal saline can increase the surrounding impedance and thus decrease the loss of RF to the surrounding environment, allowing for greater RF delivery ( Figure 1B). 25,34 With regard to environmental impedance, this may be of greater importance in the epicardium, given the presence of intrapericardial fluid and epicardial fat.…”
Section: Modulators Of Energy Sourcementioning
confidence: 99%
“…Results show a high rate of acute success among those treated, although steam pops were noted in 12 cases . Effect of environmental impedance can also alter lesion size with higher impedance surrounding RF catheters facilitating more effective RF energy delivery . This may have implication on use of high impedance supported ablation in the epicardium.…”
Section: Introductionmentioning
confidence: 99%